2003
DOI: 10.1046/j.0818-9641.2002.01148.x
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor exhibits a pronounced circadian rhythm relevant to its role as a glucocorticoid counter‐regulator

Abstract: SummaryIn humans, maximal expression of T helper 1 cytokines coincide with the nocturnal nadir of plasma cortisol, whereas T helper 2 cytokine responses are dominant during day-time. The pro-inflammatory cytokine, macrophage migration inhibitory factor counter-regulates glucocorticoid-mediated immune suppression. To determine the relationship between cortisol and macrophage migration inhibitory factor, healthy volunteers had blood drawn hourly for 24 h for measurement of plasma cortisol and basal-and stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 31 publications
2
68
3
Order By: Relevance
“…2,9,[13][14][15][16] Although our study population had considerably higher mean MIF values than those reported in other studies and our small reference group, most of the weight management participants did not have a markedly elevated plasma MIF concentration. Thus, the elevated mean group MIF in the weight management group was due to small portion of the total sample, as supported by the distribution of MIF (Figure 1).…”
Section: Mif and Associationsmentioning
confidence: 83%
“…2,9,[13][14][15][16] Although our study population had considerably higher mean MIF values than those reported in other studies and our small reference group, most of the weight management participants did not have a markedly elevated plasma MIF concentration. Thus, the elevated mean group MIF in the weight management group was due to small portion of the total sample, as supported by the distribution of MIF (Figure 1).…”
Section: Mif and Associationsmentioning
confidence: 83%
“…Attractive candidates are steroid hormones. Indeed, estradiol, progesterone, and glucocorticoids are expressed at particularly high levels during the neonatal period; have a short half-life; and stimulate MIF production by immune cells in vitro and in vivo (27,47,48). Because newborn whole blood and monocytes show somewhat different MIF secretion profiles in response to E. coli and GBS, T cells, B cells, neutrophils, eosinophils, and platelets may participate to release MIF in response to microbial stimulation (49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MIF release is triggered rather than suppressed by glucocorticoids in multiple cell types, and plasma MIF levels fluctuate in a circadian fashion that mirrors plasma levels of glucocorticoids (19,22). These properties have led some to suggest that MIF's primary function is as an endogenous counter-regulator of glucocorticoids (23).…”
Section: Macrophage Migration Inhibitory Factor (Mif)mentioning
confidence: 99%
“…MIF is ubiquitously expressed and detectable in plasma at nanogram/ml concentrations (22,33). Although MIF deletion is beneficial in multiple disease conditions, the MIF KO animal is healthy and long-lived, and in the absence of intervention it has no associated health problems (8,10,34).…”
Section: Macrophage Migration Inhibitory Factor (Mif)mentioning
confidence: 99%